Pengaruh Bore Up, Variasi Busi Racing, dan Silencer Free Flow terhadap Performa Sepeda Motor 135 cc - Ivan Nauval Mahaendra; Wahyudi Wahyudi; Febrian Arif Budiman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to test the effect of the combination of bore up, variations of racing spark plugs, and free flow exhaust silencers on engine power and torque. The method used in this study is an experimental method with a quantitative approach. Changing the bore up piston diameter from 54 mm to 62 mm makes 135 cc to 177 cc and added by varying the racing spark plugs namely iridium, platinum, and the length of the free flow exhaust silencer 180 mm and 300 mm using a dynotest test. The results of the bore up of standard spark plugs and standard exhaust increased torque by 15.06 Nm and power to 12.47 kW. The combination of bore up with iridium spark plugs and 180 mm silencers produced the highest performance, namely 16.39 Nm of torque increased by 60.50% and 15.58 kW of power increased by 100%. Meanwhile, the combination with platinum spark plugs and 300 mm silencers produced 16.04 Nm of torque and 14.61 kW of power. These findings indicate that a bore-up configuration with iridium spark plugs and a 180 mm silencer is the most optimal combination for improving engine performance.